Analisis Faktor Eksternal Organisasi dalam peningkatan Kinerja Pegawai (Studi Kasus pada Dinas Dukcapil Kabupaten Bireuen) - Purnamasari, Nini; Iba, Zainuddin; Musrizal, Musrizal (Singkite Journal, 2025)
Employee performance issues are related to external factors and the work environment, including personal communication, work relationships, and employee well-being. This study, conducted on 48 employees at the Bireuen Regency Population and Civil Registry Office, used a quantitative associative research method. Using path analysis, it was found that: (1) employee performance is determined by communication, work relationships, and well-being, with significant and positive partial effects of 54.66%, 40.86%, and 52.81%, respectively. (2) These three factors simultaneously contribute positively to each other, amounting to 80.1%. (3) There is a causal relationship between the variables of communication, work relationships, and well-being, with a fairly strong categorization.